2022
DOI: 10.1002/cam4.5270
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported disruptions to cancer care during the COVID‐19 pandemic: A national cross‐sectional study

Abstract: Background The aim of this study is to evaluate the extent and associations with patient‐reported disruptions to cancer treatment and cancer‐related care during the COVID‐19 pandemic utilizing nationally representative data. Methods This analysis uses data from the 2020 National Health Interview Survey (NHIS), an annual, cross‐sectional survey of US adults. Adults (age >18) who reported requiring current cancer treatment or other cancer‐related medical care in the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
2
8
2
Order By: Relevance
“…In contrast to previous reports, 9,10,35 we did not find any unadjusted associations between patient frailty, gender or age, and reporting a Covid-related change in care ( P = .63-.75). This likely reflects that the incidence of Covid serious infection in our jurisdiction was comparatively low and maintenance of cancer care was prioritized, 36 so there may have been less need to triage care delivery than in other jurisdictions.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to previous reports, 9,10,35 we did not find any unadjusted associations between patient frailty, gender or age, and reporting a Covid-related change in care ( P = .63-.75). This likely reflects that the incidence of Covid serious infection in our jurisdiction was comparatively low and maintenance of cancer care was prioritized, 36 so there may have been less need to triage care delivery than in other jurisdictions.…”
Section: Discussioncontrasting
confidence: 99%
“…This is not without reason. Thus, preventive medical efforts such as screening, extra isolation strategies, specialized vaccinations, or pertinent systemic therapies normally made available to cancer patients were curtailed based on competing risk to allow hospitals and health systems to effectively combat the surge of COVID-19 cases [ 14 , [15] , [16] , [17] ]. As a result, a review of the impact of COVID-19 on diagnosis and treatment of cancers revealed that there was a 27% decrease in diagnosis of cancers throughout the pandemic [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…There has been major concern regarding the impact of COVID-19 on essential health services, particularly cancer management. Patients with cancer experienced pandemic-related delayed appointments, canceled screening tests, or unexpected changes in treatment plans, among others [ 1 3 ]. Nevertheless, cancer management is extremely time-sensitive, and delays in treatment plans may lead to unintended repercussions.…”
Section: Introductionmentioning
confidence: 99%